Epoxy phenol novolac resin: A novel precursor to construct high performance hard carbon anode toward enhanced sodium-ion batteries. (5th March 2023) - Fan, Changling; Zhang, Ruisheng; Luo, Xianghua; Hu, Zhuang; Zhou, Wang; Zhang, Weihua; Liu, Jinshui; Liu, Jilei
Abstract: Although hard carbon has been considered as one of the most promising anodes for sodium-ion batteries, however, the poor performance and ambiguous sodium storage mechanism limit the further development. Herein, a novel epoxy phenol novolac resin is used as precursor for the first time to construct excellent electrochemical performance anode by pyrolyze it at different temperature. The results demonstrate that the plateau region in discharge curve of hard carbon is ascribed to Na insertion into the long-range ordered carbon structure. Improving ordering degree with suitable interlayer distance can both enhance the plateau capacity and total capacity. With the increasing of pyrolysis temperature, the graphitization degree of hard carbon is gradually enhanced. The cured epoxy phenol novolac resin pyrolyzed at 1800 °C delivers the reversible capacity of 480.3 mAh g −1 at 50 mA g −1, high initial coulombic efficiency of 84.6%, and capacity retention of 92% after 1000 cycles at 500 mA g −1 . The "adsorption-intercalation mechanism" for Na storage in EPNHC-1800 is verified by in-situ Raman spectroscopy analysis. We believe that the sodium storage mechanism of hard carbon is "adsorption-intercalation-filling", namely, the adsorption of Na-ions on the surface of carbon layers providing the slope capacity, the intercalation of Na-ions between carbon layers and filling in the nanopores providing the plateau capacity. This study offers a novel precursor to synthesize low cost and high-performance hard carbon anode material for sodium-ion batteries, delivering great opportunity for the commercialization of anode. Graphical abstract: Image 1 Highlights: Hard carbon is constructed by using novel epoxy phenol novolac resin as precursor. The structural evolution of hard carbon from precursor is studied systematically. The anode delivers the high reversible capacity of 480.3 mAh g −1 at 50 mA g −1 . The anode material shows remarkable capacity retention of 92% after 1000 cycles. "Adsorption-intercalation-filling" is dominated in the sodium storage mechanism.